Indigenous Rights of Children among Agropastoral Communities in Southern Ethiopia. (August 2022) - Jirata, Tadesse Jaleta
This article offers insights into the social and cultural rights that children are entitled to among agro-pastoral communities in Ethiopia. From an Indigenous, bottom-up perspective, children's "unwritten rights" are not just part of the customary rights and cultural practices but also exemplify local epistemologies that subvert the universal conceptualization of rights. Based on ethnographic data from Guji in Ethiopia's south, this article critically discusses the multiple rights and obligation that children have in communities that experience indigenous ways of life.